Allelopathic effect of aqueous extracts of Tithonia Rotundifolia P.M. Blake And Murraya Koenigii L. on the growth and biochemical constituents of capsicum annuum L. and corchorus olitorius L. - Tijani, Musa Oyebamiji (Obafemi Awolowo University, 2019)
xvi, 106p